Candida Esophagitis in a Male Homosexual with Defective Neutrophil Function. A 'Pseudo-AIDS' Syndrome - Michael A Noble; J Scott Whittaker; Anil K Mangal; Cedric J Carter; Hugh J Freeman (Canadian Journal of Gastroenterology, 1987)
36-year-old male homosexual presented with a prolonged history of odynophagia. Esophageal candidiasis was suspected at endoscopy and confirmed by biopsy ane cultures. Investigations demonstrated no evidence for underlying human immunodeficiency virus (HIV) infection hy either ELISA assay or Wes1ern Blot technique, and lymphocyte helper: supressor ratios were normal. A specific serum-dependent factor that inhibited the candidacidal capability of his neutrophils, as well as those of volunteer controls, was detected. This inhibitor disappeared after treatment of the candidal infection. Severe and extensive esophagitis is not always indicative of an underlying infection with HIV in homosexual mnles. Clinical criteria alone should not be used to establish the diagnosis of AIDS, even in patients from recognized high risk categories.